‘Holy Entrepreneur’: Agilbert, a Merovingian Bishop between Ireland, England and Francia - Hammer, Carl I. (Peritia, 2011)
Abstract Agilbert born in 610 into a Neustrian family influenced by Columbanus, went to southern Ireland where he studied scripture and was ordained bishop. He was a missionary bishop in Wessex c.648-60, when he returned to Francia. He headed the Roman delegation at the synod of Whitby in 664 and ordained Wilfrid priest. Before becoming bishop of Paris in 668, he was also instrumental in Wilfrid’s consecration as bishop, and may have been responsible for Wilfrid’s involvement in the return of the Merovingian royal, Dagobert II, from Ireland to Francia in 676. This paper gives a context for Agilbert’s reported activities and associations in Ireland, England and Francia and concludes that these are plausible within the pluralistic christianity of the seventh century.